Effects of a soft prefabricated thumb orthosis in carpometacarpal osteoarthritis. (January 2014) - Hermann, Merete; Nilsen, Tove; Eriksen, Camilla S.; Slatkowsky-Christensen, Barbara; Haugen, Ida Kristin; Kjeken, Ingvild
Abstract Aims: To explore the feasibility and assess the effect of a prefabricated soft thumb-base orthosis on pain, hand strength, and activity performance in persons with osteoarthritis of the CMC joint. Methods: In this randomized controlled trial, 29 patients received hand exercises only (control group) and 30 patients received hand exercises and an orthosis (orthosis group). The primary outcome was pain, while secondary outcomes included grip and pinch strength, and self-reported symptoms and activity performance. Outcome assessments, and measures of grip strength and pain with and without orthosis in the orthosis group, were made after two months. Results: 55 participants (mean age 70.5 years) completed all assessments. There were no significant differences between the groups in primary or secondary outcomes after two months. However, in the orthosis group, pain was significantly less when wearing the orthosis than when not wearing it. Participants reported that the orthosis felt uncomfortable during activities involving water and one-third wanted more support of the CMC joint. Conclusions: A soft prefabricated orthosis seems to have an immediate pain-relieving effect during use, but no effects in terms of less hand pain, or improved strength or activity performance when not worn.